Requirement of UAP56, URH49, RBM15, and OTT3 in expression of Kaposi sarcoma-associated herpesvirus ORF57 - Majerciak, Vladimir (2010)
Transport of mRNA from the nucleus to the cytoplasm is mediated by cellular RNA export factors. In this report, we examined how RNA export factors UAP56 and URH49, and RNA export cofactors RBM15 and OTT3, function in modulating KSHV ORF57 expression. We found that knockdown of each factor by RNAi led to decreased ORF57 expression. Specifically, reduced expression of either UAP56 or RBM15 led to nuclear export deficiency of ORF57 RNA. In the context of the KSHV genome, the near absence of UAP56 or RBM15 reduced the expression of both ORF57 and ORF59 (an RNA target of ORF57), but not ORF50. Collectively, our data indicate that the expression of KSHV ORF57 is regulated by cellular RNA export factors and cofactors at the posttranscriptional level.